Persistent Organic Pollutants (POPs) in Antarctica: Occurrence in continental and coastal surface snow - VECCHIATO, MARCO; ARGIRIADIS, ELENA; ZAMBON, STEFANO; BARBANTE, Carlo; TOSCANO, Giuseppa; GAMBARO, Andrea; PIAZZA, Rossano (Microchemical Journal, 2015)
Despite geographical isolation and almost complete absence of human settlements, Antarctica is affected by Persistent Organic Pollutants (POPs): the traces of these impacts are recorded in the snow. Although POPs were detected in Antarctica decades ago, there are still large knowledge gaps and a comprehensive understanding of their fundamental patterns is lacking. In this study, polychlorinated dibenzo-p-dioxins and dibenzofurans (PCDD/Fs), polychlorinated biphenyls (PCBs, including the non-Aroclor PCB-11), polybrominated diphenyl ethers (PBDEs) and polycyclic aromatic hydrocarbons (PAHs) were measured in surface snow samples from five selected locations of Northern Victoria Land. To our knowledge this is the first study providing ground-based measurements of PCDD/Fs, PCB-11 and PBDEs in Antarctic surface snows, including the plateau. Long-range atmospheric transport (LRAT) followed by regional redistribution were hypothesized as governing sources of POPs to the Antarctic Plateau, but also local pollution from human activities was found. Sub-pgL-1 levels of PCDD/Fs were detected in the coastal samples, while PCBs (σPCBs 110-580pgL-1) generally showed a decrease with respect to the past decades. Similar concentrations of PBDEs (σBDEs 130-340pgL-1) were found, mainly attributable to the congeners BDE-47 and BDE-99. PAHs (σPAHs 0.65-140ngL-1) were the most abundant compounds in all sites with an unexpected high value near a refueling point. Possible source areas of contamination were investigated by means of the HYSPLIT model. Despite geographical isolation and almost complete absence of human settlements, Antarctica is affected by Persistent Organic Pollutants (POPs): the traces of these impacts are recorded in the snow. Although POPs were detected in Antarctica decades ago, there are still large knowledge gaps and a comprehensive understanding of their fundamental patterns is lacking. In this study, polychlorinated dibenzo-p-dioxins and dibenzofurans (PCDD/Fs), polychlorinated biphenyls (PCBs, including the ...